Analysis of Teachers' Understanding of the Implementation of the Independent Curriculum in Grade IV of SDN 1 Banawa Selatan - Hidayat, Wahyu; Nasrullah, Nasrullah; Muchdar, Muchdar; Firmansyah, Arif; Boroallo, Rangga Putera (Journal of Educational Sciences, 2025)
The implementation of the independent curriculum is an approach applied in the education system to provide greater flexibility to educators and students in the teaching and learning process. The success of the learning process depends on the teacher's understanding of the curriculum concept being applied. SDN 1 Banawa Selatan uses the independent curriculum in the 2024/2025 academic year. This study aims to describe the teacher's understanding of the implementation of the independent curriculum in class IV of SDN 1 Banawa Selatan. This study uses a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the implementation of the Independent Curriculum has been running but has not been optimal due to several obstacles, especially related to the teacher's understanding which is not optimal in accordance with the independent curriculum, the lack of adequate supporting facilities to support the implementation of the independent curriculum in accordance with procedures, and also limited training for teachers. So that the implementation of the independent curriculum is not implemented in accordance with the indicators in the independent curriculum.